(untitled) (Journal of Economic Research & Business Administration, 2020)
Currency regulation plays a significant role in the state economic policy. Depending on the goal, currency regulation can stimulate or constrain economic development in the country and, accordingly, affect the state of individual sectors, industries and enterprises, as well as the place of the state in the world market. In modern conditions of economic globalization, the exchange rate is becoming one of the main integrated macroeconomic indicators, which affects not only the foreign economic activity of the state, but also, in general, the socio-economic development of our country. The imbalance of the foreign exchange market, the negative trade balance, high inflation rates indicate that the problem of conducting an effective exchange rate policy and establishing the optimal level of the exchange rate remains unresolved. It is necessary to choose the optimal system for regulating the rate of currency quotations to solve these problems. The paper discusses theoretical approaches to the system of regulation of exchange rate regimes. Systematized and classified methods of currency regulation. The proposed application of a systematic approach to the stabilization of the exchange rate, which promotes the integrity, hierarchy, structuring of currency systems. And this paper also discusses the problems of currency regulation and ways to overcome them.